A Review on Equipment Protection and System Protection Relay in Power System - Hui Hwang, Goh (International Journal of Integrated Engineering, 2017)
Power system equipment is configured and connected together with multiple voltage levels in existing electrical power system. There are varieties of electrical equipment obtainable in the power system predominantly from generation side up to the distribution side. Consequently, appropriate protections must be apt to prevent inessential disturbances that lead to voltage instability, voltage collapse and sooner a total blackout took place in the power system. The understanding of each component on the system protection is critical. This is due to any abnormal condition and failure can be analyzed and solved effectively due to the rapid changing and development on the power system network. Therefore, the enhancement of power quality can be achieved by sheltering the equipment with protection relay in power system. Moreover, the design of a systematic network is crucial for the system protection itself. Several types of protective equipment and protection techniques are taken into consideration in this paper. Hence, the existing accessible types and methods of system protection in the power system network are reviewed.